Patent prescription a radical cure for the ailing [US patent policy]. - Jaffe, A.B (IEEE spectrum)
This work discusses the problems with the current patent system in the US. While the US patent policy makes it easier to obtain patents, to enforce patents against others, and to extract large financial awards from such enforcement, it has become harder for those accused of infringing patents to challenge the patents' validity. To address the problem, a patent policy reform program was initiated based on three proposals: first, create incentives and opportunities for parties to challenge the novelty and nonobviousness of an invention before a patent is granted, second, provide multiple levels of application review, with examiners devoting successively more time and effort as an application proceeds to higher levels, and third, in cases involving claims of patent invalidity based on the existence of prior act, replace juries with judges who could call on experts for guidance. The first two proposals aim to make the PTO more effective at a reasonable cost. The third addresses the reality that since even the best of all possible PTOs will make mistakes, a court system capable of correcting them is necessary.